The Comparison Between Rantau Keloyang Dialect and Sungai Beringin Dialect (Phonological Point of View) - Vera Magria; Asridayani Asridayani; Eli Suryani (Jurnal Ilmiah Langue and Parole, 2023)
This research investigates about phonetic differences between Rantau Keloyang Dialect and Sungai Beringin Dialect. The purpose of the research are (1) to know about the differences between Rantau Keloyang Dialect and Sungai Beringin Dialect in term of vowel, consonant and Diphthong and (2) to identify the differences of phoneme between Rantau Keloyang Dialect and Sungai Beringin Dialect. Data are gained through eliciting, participating and note taking technique. Data are analyzed based on theories proposed by Crowley (1987). The result of this research show that the differences of phoneme in both dialects are occurred due phonemic change, diphthong, and phonemic addition as well as deletion.the differences happen due to the influence of Jambinese language in rantau Keloyang dialect and Minangese Language for Sungai Beringin Dialect